Strengthening the community seed banks in South Africa - Mokoena, Mpolokeng Lydia; Sema, P.R.; Maluleke, Nkat Lettie; Tjikana, Thabo T.; Dibiloane, M.A.; Vernooy, Ronnie (2019)
Since 2013, DAFF and Bioversity International have been working together to establish and support community seed banks as a means to strengthen farmers’ seed systems, support conservation and sustainable use of traditional farmers’ varieties and maintain seed security at district and community levels in the Republic of South Africa. Three community seed banks have been set up in Gumbu, Sterkspruit and Jericho. This report describes the main activities carried out in 2018-2019. Farmers of the Jericho community seed bank, which was inaugurated in 2019, were trained in seed bank management techniques. Farmers of the three community seed banks multiplied seed of selected crop varieties stored in the three community seed banks. Despite shortage of water and excessive heat in most parts of South Africa, farmers still show an interest and eagerness in making agriculture the primary vehicle to improve their rural livelihoods and fight hunger. The challenges of climate change are affecting the development of crops and limit farmers’ increase of production and yields. There is a need to continue providing support to farmers and the community seed banks at all three sites (Gumbu, Jericho and Sterkspruit) in order to strengthen and improve their knowledge and farming skills.